A life course study of the effects of experienced life events on the onset and continuity of preventive healthcare behaviors. Issue 1 (2nd January 2019) - Yingwattanakul, Preecha; Moschis, George P.
Abstract: This study offers the life course paradigm as a viable framework for studying the onset and continuity of three preventive healthcare behaviors at different stages in life. The results reveal that life events experienced earlier in life significantly affect the likelihood of the onset of some certain behaviors and have a different impact on the risk of discontinuation of such a behavior at different life stages. The findings also support the notion that the longer people engage in a certain preventive healthcare activity, the more likely they are to continue that activity. Implications for research and practice are discussed.